Minimum wage: Labour market consequences in the Czech Republic - Kamila Fialová; Martina Mysíková (Charles University in Prague, Institute of Economic Studies (IES), 2009)
This paper aims to quantify the impact of the minimum wage on labour market performance in the Czech Republic. Using regional data for 1995-2004, it estimates the effect of the minimum wage adjusted for regional wage differential on the regional unemployment. Consequently, using detail individual data from 2004/2005, we analyze the annual hikes in the minimum wage that allow us to estimate employment probabilities for workers with wage level at, or close to, the new minimum wage. The aim is to reveal whether the most endangered groups of workers exhibited significantly different employment probabilities. Our results reveal that the minimum wage has had a significant impact on increasing regional unemployment and reducing the employment probabilities of low-paid workers.
Keywords: E24; J38; J64; 330; minimum wage; employment probability; unemployment; Mindestlohn; Arbeitsmarkt; Arbeitslosigkeit; Tschechische Republik